Preparation method of spectrum-adjustable flexible cellulose-based aerogel material

Through the spectrals preparation of the co-ahead and solitary-gel legal system, the flexible cellulose base gas gel material can be adjusted, and infrared shielding agents and ultraviolet absorbers are added to solve the solar energy of cellulose base gas gel material in the energy saving and cooling application. The absorption problem has achieved efficient thermal insulation performance and extensive application potential.

CN119350702APending Publication Date: 2025-01-24NANJING TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411638754.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The application of cellulose-based aerogel materials in achieving energy-saving cooling has been hindered, especially in the issue of solar energy absorption, and existing materials are difficult to effectively improve thermal insulation performance.

Method used

By adopting the pre-driven method, the solution-gel method and drying process, a spectrum can regulate the material of flexible cellulose base gas, add infrared shielding agent and ultraviolet absorbent to optimize the optical performance of the material.

Benefits of technology

The prepared gas gel material has flexible, high -light selectivity, low heat -conducting coefficient and high -ratio surface area, which significantly improves thermal insulation performance and broaden its application in building glass, energy -saving windows, and new energy batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350702A_ABST
    Figure CN119350702A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of preparation processes of nano-porous materials, and relates to a preparation method of a spectrum-adjustable flexible cellulose-based aerogel material. The preparation method comprises the following steps: dissolving cellulose in an ionic liquid to obtain a sol solution, sequentially introducing an organic silicon source modifier, an infrared screening agent and an ultraviolet absorbent into the sol solution, and carrying out a molding process, aging and drying to obtain the spectrum-adjustable flexible cellulose-based aerogel material. The method has the advantages of green and low-cost materials and convenient process, and is low in energy consumption, simple in process and easy to realize large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of aerogel material preparation technology, and specifically relates to a method for preparing a spectrally adjustable flexible cellulose-based aerogel material by adopting a co-precursor method, a sol-gel method and a drying process. Background Art

[0002] Cellulose is the most abundant natural polysaccharide polymer in nature. It is composed of D-pyranose glucose units connected by β-1,4 glycosidic bonds and is widely present in the cell wall structure of higher plants such as wood, cotton, linen, and bamboo. Cellulose has attracted the attention of researchers around the world because of its biodegradability, environmental friendliness, and natural renewability. Many cellulose-based materials have been developed and applied. Among them, cellulose-based aerogel is a solid lightweight material with a three-dimensional nanoporous network structure. It has the advantages of low density, high porosity, high specific surface area, low thermal conductivity, and sustainability. It has broad application prospects in energy-saving buildings, oil adsorption, thermal insulation, and other fields. Cellulose-based aerogel films are prepared by film-forming processes such as casting, impregnation, spin coating, spraying, and simple brushing. They not only retain most of the excellent properties of bulk aerogels, but also expand their application channels due to their unique film structure, such as personal wearable devices, new energy batteries, supercapacitor electrode materials, phase change materials, etc.

[0003] The heat transfer of cellulose-based aerogels usually includes heat conduction, heat convection and heat radiation. According to Kdnusen diffusion, the thermal conductivity of cellulose aerogels is closely related to their density, pore size and surface structure. However, the radiant energy of sunlight mainly comes from the visible light and near-infrared regions, and the application of cellulose-based aerogels in achieving energy-saving cooling is hindered. In order to improve the thermal insulation performance of cellulose-based aerogel materials and give full play to their advantages, the cooling materials explored recently include: multilayer photonic structures, nanocomposite films, polymer materials and hybrid optical metamaterials, but these materials are still struggling to solve the problem of solar energy absorption. Therefore, it is a good method to introduce functional additives such as ultraviolet absorbers and infrared shielding agents into cellulose-based aerogel materials to improve the thermal insulation performance of aerogel films and reduce the thermal radiation energy of transmitted light. Yu et al. studied an optically selective aerogel containing silver nanocylinders and infrared shielding agents. The results show that the composite aerogel can penetrate visible light and absorb solar infrared radiation at the same time, which provides guidance for the preparation of optically selective aerogels with high spectral tuning performance and has important application value in the multi-spectral conversion of solar radiation. However, the aerogel obtained by the above method lacks certain flexibility and transparency, and its application range is greatly limited. The long cellulose chain in cellulose-based aerogel plays a supporting role, and the prepared aerogel material has certain flexibility and excellent mechanical properties and thermal insulation properties. Without affecting its own performance, the clever use of functional additives to enhance the optical properties of cellulose aerogel materials can broaden the application range of this material. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a spectrally adjustable flexible cellulose-based aerogel material in order to improve the thermal insulation and optical selectivity of cellulose aerogel materials. The method has simple raw materials and processes, low energy consumption, and controllable structure. The prepared aerogel material has the characteristics of flexibility, flame retardancy, low density, low thermal conductivity, high specific surface area, high optical selectivity, etc., and has positive production significance for realizing the application of aerogel materials in the fields of architectural glass, energy-saving windows, new energy batteries, supercapacitor electrode materials, personal wearable devices, and biomedical carriers.

[0005] The technical solution of the present invention is a method for preparing a spectrally adjustable flexible cellulose-based aerogel material, and the specific steps are as follows:

[0006] (1) adding cellulose to the ionic liquid at a mass ratio of cellulose to ionic liquid of 1:(5-500), and uniformly stirring at 50-85° C. for 0.5-5 h to obtain a transparent cellulose sol system;

[0007] (2) adding the organosilicon source modifier to the cellulose sol system obtained in step (1) at a mass ratio of the organosilicon source modifier to the cellulose sol of 1:(2-50), and uniformly stirring at 50-85° C. for 0.5-5 h to obtain a cellulose sol solution A;

[0008] (3) adding the infrared shielding agent and the ultraviolet absorber to the cellulose sol solution A in step (2) at a mass ratio of the infrared shielding agent to the cellulose sol solution A of 1:(10-5000) and a mass ratio of the ultraviolet absorber to the cellulose sol solution A of 1:(5-5000), and uniformly stirring the mixture at 50-85° C. for 0.5-5 h to obtain a cellulose-based sol solution B;

[0009] (4) placing the cellulose-based sol solution B obtained in step (3) into a vacuum drying oven for degassing to obtain a treated cellulose-based sol solution C;

[0010] (5) loading the cellulose-based sol solution C obtained in step (4) into a molding process device to prepare a spectrum-adjustable cellulose-based sol block or film;

[0011] (6) placing the spectrum-adjustable cellulose-based sol block or film obtained in step (5) into an ionic liquid aqueous solution with a mass percentage of 5% to 90% to obtain a spectrum-adjustable regenerated cellulose-based wet gel block or film;

[0012] (7) adding the spectrum-adjustable regenerated cellulose-based wet gel block or film obtained in step (6) into an aging solution for solvent replacement to prepare a spectrum-adjustable cellulose-based alcohol gel block or film;

[0013] (8) Drying the spectrum-adjustable cellulose-based alcohol gel block or film obtained in step (7) to obtain a spectrum-adjustable flexible cellulose-based aerogel block or film material.

[0014] Preferably, the cellulose in step (1) is one or more of celluloses derived from wood, cotton, cotton linters, wheat straw, hemp, bamboo, rice straw, reed, mulberry bark, paper mulberry bark or bagasse.

[0015] Preferably, the ionic liquid described in step (1) is an organic molten salt at room temperature or near room temperature (below 100° C.) formed by cations and anions of imidazoles, pyridines and quaternary ammonium salts, and is one or more of [HMIm]Cl, [Hbim]Cl, [Hemim]Cl, [Emim]BF4, [Emim]Tf2N, [Emim]OAc, [Mmim](MeO)2PO2, [Pmim]Cl, [Bmim]PF6, [BzMim]BF4, [Bmim]MeSO4, [Bmim]HSO4, [Amim]Cl, [Epyr]BF4, [Bpyr]PF6, [Mpyr]Cl, [Empy]Tf2N, [PhPy]BF4 or [Et3NH]HSO4.

[0016] Preferably, the organosilicon source modifier described in step (2) is one or a combination of two or more of water glass, tetraethyl orthosilicate (TEOS), methyl orthosilicate (TMOS), methyltriethoxysilane (MTES), methyltrimethoxysilane (MTMS), polyethoxydisiloxane (PEDS), dimethyldimethoxysilane (DMDMS), dodecyltrimethoxysilane (DTMS) or polydimethylsiloxane (PDMS).

[0017] Preferably, the infrared shielding agent described in step (3) is a functional particle formed by inorganic nanoparticles having near-infrared shielding ability, such as LaB6, CuS, PbS, ZnS, Si3N4, TiO2, M x One or more combinations of WO3 (M = Na, Li, K, Rb, Cs), ITO, ATO or AZO.

[0018] Preferably, the ultraviolet absorber in step (3) is one or more combinations of UV-P, UV-O, UV-9, UV-326, UV-328, UV-531, UVP-327, RMB, AM-101 or GW-540.

[0019] Preferably, the temperature of the vacuum drying oven in step (4) is 50-85°C, the vacuum degree is 0.01-0.1MPa, and the insulation time is 1-5h; the molding process device in step (5) is: casting method, immersion-pulling method, spin coating method or spraying method. Preferably, the process parameters of the casting method are: casting rate of 1-300ml / min, casting time of 1-5min; the process parameters of the immersion-pulling method are: pulling rate of 0.1-2cm / s, pulling time of 1-3min; the process parameters of the spin coating method are: rotation rate of 300-2000rpm, spin coating acceleration of 50-500rpm / sec, spin coating time of 0.5-3min; the process parameters of the spray coating method are: spraying rate of 1-200ml / min, spraying time of 1-10min.

[0020] Preferably, the aging liquid in step (7) is one of methanol, anhydrous ethanol, n-propanol, isopropanol, butanol, n-pentanol, hexanol, cyclohexanol or tert-butanol, or a mixture thereof; the solvent replacement is carried out at room temperature, the number of replacements is 2 to 5, and the interval between each replacement is 2 to 6 hours.

[0021] Preferably, the drying method in step (8) is atmospheric pressure drying, freeze drying, and carbon dioxide supercritical drying; the process parameters of the atmospheric pressure drying method are: the temperature is continuously increased under atmospheric pressure to evaporate the solvent, the temperature is 25-80°C, and the drying time is 12-48h; the process parameters of the freeze drying method are: the frozen solvent is sublimated under negative pressure, the freezing temperature is -80--20°C, the partition temperature is 15-30°C, and the drying time is 24-48h; the process parameters of the carbon dioxide supercritical drying method are: carbon dioxide is used as the drying medium, the temperature is 45-50°C, the pressure in the high-pressure reactor is 9-12MPa, the degassing rate is 2-8L / min, and the drying time is 6-12h.

[0022] Beneficial effects:

[0023] (1) Green raw materials, simple process, and low energy consumption. Cellulose gel is modified by organic silicon source modifier and functional additive, and the sol-gel method is adopted, and then a spectrally adjustable flexible cellulose-based aerogel material is generated through subsequent drying treatment.

[0024] (2) The material has the characteristics of flexibility, high optical selectivity, high porosity, high specific surface area and uniform particles, which has positive significance for the application of aerogel materials in architectural glass and energy conservation fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a physical photograph of the spectrally tunable flexible cellulose-based aerogel material prepared in Example 1.

[0026] Figure 2This is an absorbance curve of the spectrally tunable flexible cellulose-based aerogel material prepared in Example 1.

[0027] Figure 3 This is a transmittance curve of the spectrally tunable flexible cellulose-based aerogel material prepared in Example 1. DETAILED DESCRIPTION

[0028] Example 1

[0029] Add 0.1g of cotton pulp to 5g of AmimCl-type ionic liquid and stir at 80℃ for 0.5h to obtain a uniform and transparent cellulose sol. Add 1g of methyltriethoxysilane to the cellulose sol and stir at 80℃ for 0.5h to obtain a uniform cellulose sol solution A. Add 0.0051g of ITO and 0.0102g of UV-326 to the cellulose sol solution A and stir at 80℃ for 0.5h to obtain a uniform cellulose sol solution B. Vacuum and keep warm in a vacuum oven at 80℃ for 1h with a vacuum degree of 0.01MPa to obtain a cellulose-based sol solution C. Pour the cellulose-based sol solution C into a mold, put the mold into a spin coater, spin coat it into a thin film, and let it stand at a speed of 400rpm, an acceleration of 500rpm / sec, and a time of 45s to obtain a spectrally adjustable cellulose-based sol film. Prepare a 60wt% AmimCl ionic liquid aqueous solution and pour it into the mold. After gelation, demold and take it out to obtain a spectrally adjustable regenerated cellulose-based wet gel film. Use anhydrous ethanol to replace it in sequence, replace it once every 4 hours, and replace it twice to obtain a spectrally adjustable cellulose-based alcohol gel film. Then the alcohol gel film is supercritically dried with carbon dioxide, wherein the reaction temperature is 50°C, the pressure in the high-pressure reactor is 10MPa, the degassing rate is 5L / min, and the drying time is 6h, thereby obtaining a 0.5mm spectrally adjustable flexible cellulose-based aerogel film. The thermal conductivity of the obtained film material is 0.0184W·m -1 ·K -1 , near infrared absorbance is 0.91, the actual photo is as follows Figure 1 As shown. Figure 2 It can be seen that its UV absorbance is 2.36; Figure 3 It can be seen that its transmittance is 91.5%.

[0030] Example 2

[0031] Add 0.01g of cotton pulp to 5g of [HMIm]Cl type ionic liquid, stir at 50℃ for 0.5h to obtain a uniform and transparent cellulose sol. Add 1.5g of methyltrimethoxysilane to the cellulose sol, stir at 50℃ for 0.5h to obtain a uniform cellulose sol solution A. Add 0.001302g of ATO and 0.015g of UV-P to cellulose sol solution A, stir at 50℃ for 0.5h to obtain a uniform cellulose sol solution B. Vacuum and keep warm in a 50℃ vacuum oven for 2h with a vacuum degree of 0.01MPa to obtain a cellulose-based sol solution C. Pour the cellulose-based sol solution C into a mold, put the mold into a spin coater and spin coat it into a thin film and let it stand at a speed of 300rpm, an acceleration of 50rpm / sec, and a time of 3min to obtain a spectrally adjustable cellulose-based sol film. Prepare a 15wt% [HMIm]Cl ionic liquid aqueous solution and pour it into a mold. After gelation, demold and remove it to obtain a spectrally controllable regenerated cellulose-based wet gel film. Use anhydrous ethanol to replace it in sequence, replace it once every 2 hours, and replace it 5 times to obtain a spectrally controllable cellulose-based alcohol gel film. Then, the alcohol gel film is supercritically dried with carbon dioxide, wherein the reaction temperature is 50°C, the pressure in the high-pressure reactor is 12MPa, the degassing rate is 8L / min, and the drying time is 12h, thereby obtaining a 0.6mm spectrally controllable flexible cellulose-based aerogel film. After characterization, it was found that: (1) the thermal conductivity is 0.0188W·m -1 ·K -1 , (2) near-infrared absorbance is 0.80, (3) ultraviolet absorbance is 2.03, (4) transmittance is 88.2%.

[0032] Example 3

[0033] Add 0.4g of hemp pulp to 5g of [Hemim]Cl type ionic liquid, stir at 70℃ for 1h to obtain a uniform and transparent cellulose sol. Add 2.7g of tetraethyl orthosilicate to the cellulose sol, stir at 70℃ for 3h to obtain a uniform cellulose sol solution A. Add 0.0085g of AZO and 0.01g of UV-O to cellulose sol solution A, stir at 70℃ for 3h to obtain a uniform cellulose sol solution B. Vacuum and keep warm in a vacuum oven at 70℃ for 2h, with a vacuum degree of 0.07MPa to obtain a cellulose-based sol solution C. Pour the cellulose-based sol solution C into a mold, put the mold into a spin coater, spin coat it into a thin film and let it stand, with a rotation speed of 2000rpm, an acceleration of 500rpm / sec, and a time of 0.5min to obtain a spectrally adjustable cellulose-based sol film. Prepare a 90wt% [Hemim]Cl ionic liquid aqueous solution and pour it into a mold. After gelation, demold and remove it to obtain a spectrally controllable regenerated cellulose-based wet gel film. Use anhydrous ethanol to replace it in sequence, replace it once every 3 hours, and replace it 4 times to obtain a spectrally controllable cellulose-based alcohol gel film. Then, the alcohol gel film is supercritically dried with carbon dioxide, wherein the reaction temperature is 45°C, the pressure in the high-pressure reactor is 9MPa, the degassing rate is 2L / min, and the drying time is 6h, thereby obtaining a 0.7mm spectrally controllable flexible cellulose-based aerogel film. After characterization, it was found that: (1) the thermal conductivity is 0.0189W·m -1 ·K -1 , (2) near-infrared absorbance is 0.94, (3) ultraviolet absorbance is 2.32, and (4) transmittance is 86.5%.

[0034] Example 4

[0035] Add 1g of hemp pulp to 10g of [Hbim]Cl type ionic liquid, stir at 85℃ for 1h to obtain a uniform and transparent cellulose sol. Add 0.22g of polyethoxydisiloxane to the cellulose sol, stir at 85℃ for 5h to obtain a uniform cellulose sol solution A. Add 0.01g of TiO2 and 0.015g of UV-9 to cellulose sol solution A, stir at 85℃ for 5h to obtain a uniform cellulose sol solution B. Vacuum and keep warm in a vacuum oven at 80℃ for 2.5h, with a vacuum degree of 0.1MPa, to obtain a cellulose-based sol solution C. Pour the cellulose-based sol solution C into a mold for casting, with a casting rate of 300ml / min, a casting time of 1min, and stand for 0.5h to obtain a spectrally adjustable cellulose-based sol film. Prepare a 65wt% [Hbim]Cl ionic liquid aqueous solution and pour it into the mold. After gelation, demold and remove it to obtain a spectrally adjustable regenerated cellulose-based wet gel film. The film was replaced with anhydrous ethanol in sequence, once every 2 hours, for 3 times, to obtain a spectrally tunable cellulose-based alcohol gel film. The alcohol gel film was then dried at room temperature, at 80°C, for 12 hours, to obtain a 1 mm spectrally tunable flexible cellulose-based aerogel film. Characterization revealed that: (1) The thermal conductivity was 0.0193 W·m -1 ·K -1 , (2) near-infrared absorbance is 0.90, (3) ultraviolet absorbance is 2.25, (4) transmittance is 77.6%.

[0036] Example 5

[0037] Add 5g [Hbim]Cl and 15g [Amim]Cl type ionic liquids to 0.7g of bamboo pulp, stir at 70°C for 1.5h to obtain a uniform and transparent cellulose sol. Add 3g of methyl orthosilicate to the cellulose sol, stir at 70°C for 1h to obtain a uniform cellulose sol solution A. Add 0.05g of CuS and 0.03g of UV-328 to the cellulose sol solution A, stir at 70°C for 1h to obtain a uniform cellulose sol solution B. Vacuum and keep warm in a vacuum oven at 70°C for 5h with a vacuum degree of 0.05MPa to obtain a cellulose-based sol solution C. Pour the cellulose-based sol solution C into a mold for casting at a casting rate of 1ml / min and a casting time of 5min. Let it stand for 0.2h to obtain a spectrally adjustable cellulose-based sol block. Prepare a 5wt% [Hbim]Cl ionic liquid aqueous solution and pour it into the mold. After gelation, demold and take it out to obtain a spectrally adjustable regenerated cellulose-based wet gel block. The cellulose-based alcohol gel block with adjustable spectrum was replaced with anhydrous ethanol in sequence, once every 3 hours, and replaced 4 times to obtain a spectrally adjustable cellulose-based alcohol gel block. The alcohol gel block was then dried at room temperature, at a temperature of 25°C, for 48 hours, to obtain a 2.5 mm spectrally adjustable flexible cellulose-based aerogel block. After characterization, it was found that: (1) the thermal conductivity was 0.0198 W·m -1 ·K -1 , (2) near-infrared absorbance is 0.86, (3) ultraviolet absorbance is 2.15, and (4) transmittance is 65.8%.

[0038] Example 6

[0039] Add 0.5g of pulp to 2g of [Hbim]Cl and 8g of [Hemim]Cl type ionic liquid, stir at 60°C for 1h to obtain a uniform and transparent cellulose sol. Add 2g of polydimethylsiloxane to the cellulose sol, stir at 60°C for 1h to obtain a uniform cellulose sol solution A. Add 0.04g of PbS and 0.04g of UV-531 to the cellulose sol solution A, stir at 60°C for 1h to obtain a uniform cellulose sol solution B. Vacuum and keep warm in a vacuum oven at 85°C for 1.5h with a vacuum degree of 0.04MPa to obtain a cellulose-based sol solution C. Pour the cellulose-based sol solution C into a mold for casting at a casting rate of 150ml / min and a casting time of 2.5min. Let it stand for 0.4h to obtain a spectrally adjustable cellulose-based sol block. Prepare a 65wt% [Hemim]Cl ionic liquid aqueous solution and pour it into a mold. After gelation, demold and take it out to obtain a spectrally controllable regenerated cellulose-based wet gel block. Use anhydrous ethanol to replace it in sequence, replace it once every 4 hours, and replace it 3 times to obtain a spectrally controllable cellulose-based alcohol gel block. Then freeze-dry the alcohol gel block at a freezing temperature of -20°C, a partition temperature of 30°C, and a drying time of 48 hours to obtain a 2mm spectrally controllable flexible cellulose-based aerogel block. After characterization, it was found that: (1) The thermal conductivity is 0.0196W·m -1 ·K -1 , (2) near-infrared absorbance is 0.92, (3) ultraviolet absorbance is 2.31, and (4) transmittance is 68.9%.

[0040] Example 7

[0041] Add 1g of hemp pulp to 30g of [Mpyr]Cl type ionic liquid, stir at 70℃ for 5h to obtain a uniform and transparent cellulose sol. Add 5g of dodecyltrimethoxysilane to the cellulose sol, stir at 70℃ for 2.5h to obtain a uniform cellulose sol solution A. Add 0.1g of LaB6 and 0.015g of RMB to cellulose sol solution A, stir at 70℃ for 1.5h to obtain a uniform cellulose sol solution B. Vacuum and keep warm in a vacuum oven at 70℃ for 3h with a vacuum degree of 0.1MPa to obtain a cellulose-based sol solution C. Spray the cellulose-based sol solution C onto the mold at a spray rate of 1ml / min and a spray time of 10min to obtain a spectrally adjustable cellulose-based sol film. Prepare a 5wt% [Mpyr]Cl ionic liquid aqueous solution and pour it into the mold. After gelation, demold and remove it to obtain a spectrally adjustable regenerated cellulose-based wet gel film. The film was replaced with anhydrous ethanol in sequence, once every 3 hours, and replaced 4 times to obtain a spectrally adjustable cellulose-based alcohol gel film. The alcohol gel film was then freeze-dried at a freezing temperature of -80°C, a partition temperature of 15°C, and a drying time of 24 hours to obtain a 0.3 mm spectrally adjustable flexible cellulose-based aerogel film. After characterization, it was found that: (1) the thermal conductivity was 0.0174 W·m -1 ·K -1 , (2) near-infrared absorbance is 0.96, (3) ultraviolet absorbance is 2.16, (4) transmittance is 70.8%.

[0042] Example 8

[0043] Add 0.3g of wood pulp to 25g of [Pmim]Cl type ionic liquid, stir at 80℃ for 2h to obtain a uniform and transparent cellulose sol. Add 4g of dimethyldimethoxysilane to the cellulose sol, stir at 80℃ for 2h to obtain a uniform cellulose sol solution A. Add 0.01g of Si3N4 and 0.01g of AM-101 to cellulose sol solution A, stir at 80℃ for 2h to obtain a uniform cellulose sol solution B. Vacuum and keep warm in a vacuum oven at 80℃ for 2h, with a vacuum degree of 0.01MPa to obtain a cellulose-based sol solution C. Spray the cellulose-based sol solution C onto the mold at a spray rate of 200ml / min and a spray time of 1min to obtain a spectrally adjustable cellulose-based sol film. Prepare a 60wt% [Pmim]Cl ionic liquid aqueous solution and pour it into the mold. After gelation, demold and remove it to obtain a spectrally adjustable regenerated cellulose-based wet gel film. The alcohol gel film was then supercritically dried with carbon dioxide at a reaction temperature of 48°C, a pressure of 10 MPa in the autoclave, a degassing rate of 7 L / min, and a drying time of 12 h to obtain a 0.5 mm spectrally tunable flexible cellulose-based aerogel film. Characterization revealed that: (1) the thermal conductivity was 0.0187 W·m -1 ·K -1 , (2) near-infrared absorbance is 0.89, (3) ultraviolet absorbance is 2.13, (4) transmittance is 68.3%.

[0044] Example 9

[0045] 6g of bamboo pulp was added to 15g of [Pmim]Cl and 15g of [PhPy]BF4 type ionic liquid, stirred at 50°C for 5h to obtain a uniform and transparent cellulose sol. 2g of dimethyldimethoxysilane and 3g of methyltrimethoxysilane were added to the cellulose sol, stirred at 50°C for 5h to obtain a uniform cellulose sol solution A. 4.1g of ZnS and 0.0082g of GW-540 were added to the cellulose sol solution A, stirred at 50°C for 2h to obtain a uniform cellulose sol solution B. Vacuumed and kept warm in a vacuum oven at 80°C for 2h, with a vacuum degree of 0.01MPa, to obtain a cellulose-based sol solution C. Pour the cellulose-based sol solution C into a mold, dip-pull the mold into a film and let it stand, with a pulling rate of 2cm / s and a pulling time of 3min to obtain a spectrally adjustable cellulose-based sol film. Prepare a 10wt% [PhPy]BF4 ionic liquid aqueous solution and pour it into a mold. After gelation, demold and remove it to obtain a spectrally controllable regenerated cellulose-based wet gel film. Use anhydrous ethanol to replace it in sequence, replace it once every 2 hours, and replace it 5 times to obtain a spectrally controllable cellulose-based alcohol gel film. Then, the alcohol gel film is supercritically dried with carbon dioxide, wherein the reaction temperature is 49°C, the pressure in the high-pressure reactor is 11MPa, the degassing rate is 8L / min, and the drying time is 12h, thereby obtaining a 0.6mm spectrally controllable flexible cellulose-based aerogel film. After characterization, it was found that: (1) the thermal conductivity is 0.0201W·m -1 ·K -1 , (2) near-infrared absorbance is 0.92, (3) ultraviolet absorbance is 2.29, (4) transmittance is 66.9%.

[0046] Example 10

[0047] Add 2g of bamboo pulp to 10g of [Emim]BF4 and 5g of [Mmim](MeO)2PO2 ionic liquid, stir at 70℃ for 5h to obtain a uniform and transparent cellulose sol. Add 1g of tetraethyl orthosilicate and 4g of polydimethylsiloxane to the cellulose sol, stir at 70℃ for 5h to obtain a uniform cellulose sol solution A. Add 0.0044g of Si3N4 and 4.4g of RMB to the cellulose sol solution A, stir at 70℃ for 2h to obtain a uniform cellulose sol solution B. Vacuum and keep warm in a vacuum oven at 80℃ for 4h with a vacuum degree of 0.01MPa to obtain a cellulose-based sol solution C. Pour the cellulose-based sol solution C into a mold, dip-pull the mold into a film and let it stand, with a pulling rate of 0.1cm / s and a pulling time of 1min to obtain a spectrally adjustable cellulose-based sol film. Prepare a 10wt% [Mmim](MeO)2PO2 ionic liquid aqueous solution and pour it into a mold. After gelation, demold and take out to obtain a spectrally controllable regenerated cellulose-based wet gel film. Use anhydrous ethanol to replace it in sequence, replace it once every 6 hours, and replace it twice to obtain a spectrally controllable cellulose-based alcohol gel film. Then, the alcohol gel film is supercritically dried with carbon dioxide, wherein the reaction temperature is 50°C, the pressure in the high-pressure reactor is 12MPa, the degassing rate is 7L / min, and the drying time is 10h, thereby obtaining a 0.3mm spectrally controllable flexible cellulose-based aerogel film. After characterization, it was found that: (1) the thermal conductivity is 0.0172W·m -1 ·K -1 , (2) near-infrared absorbance is 0.82, (3) ultraviolet absorbance is 2.26, (4) transmittance is 83.2%.

Claims

1. A method for preparing a spectrally tunable flexible cellulose-based aerogel material, the specific steps of which are as follows: (1) adding cellulose to the ionic liquid at a mass ratio of cellulose to ionic liquid of 1:(5-500), and uniformly stirring at 50-85° C. for 0.5-5 h to obtain a transparent cellulose sol system; (2) adding the organosilicon source modifier to the cellulose sol system obtained in step (1) at a mass ratio of the organosilicon source modifier to the cellulose sol of 1:(2-50), and uniformly stirring at 50-85° C. for 0.5-5 h to obtain a cellulose sol solution A; (3) adding the infrared shielding agent and the ultraviolet absorber to the cellulose sol solution A in step (2) at a mass ratio of the infrared shielding agent to the cellulose sol solution A of 1:(10-5000) and a mass ratio of the ultraviolet absorber to the cellulose sol solution A of 1:(5-5000), and uniformly stirring the mixture at 50-85° C. for 0.5-5 h to obtain a cellulose-based sol solution B; (4) placing the cellulose-based sol solution B obtained in step (3) into a vacuum drying oven for degassing to obtain a treated cellulose-based sol solution C; (5) loading the cellulose-based sol solution C obtained in step (4) into a molding process device to prepare a spectrum-adjustable cellulose-based sol block or film; (6) placing the spectrum-adjustable cellulose-based sol block or film obtained in step (5) into an ionic liquid aqueous solution with a mass percentage of 5% to 90% to obtain a spectrum-adjustable regenerated cellulose-based wet gel block or film; (7) adding the spectrum-adjustable regenerated cellulose-based wet gel block or film obtained in step (6) into an aging solution for solvent replacement to prepare a spectrum-adjustable cellulose-based alcohol gel block or film; (8) Drying the spectrum-adjustable cellulose-based alcohol gel block or film obtained in step (7) to obtain a spectrum-adjustable flexible cellulose-based aerogel block or film material.

2. The preparation method according to claim 1, characterized in that The cellulose in step (1) is one or more of various celluloses derived from wood, cotton, cotton linters, wheat straw, hemp, bamboo, rice straw, reed, mulberry bark, paper mulberry bark or sugarcane bagasse.

3. The preparation method according to claim 1, characterized in that The ionic liquid described in step (1) is one or more of [HMIm]Cl, [Hbim]Cl, [Hemim]Cl, [Emim]BF4, [Emim]Tf2N, [Emim]OAc, [Mmim](MeO)2PO2, [Pmim]Cl, [Bmim]PF6, [BzMim]BF4, [Bmim]MeSO4, [Bmim]HSO4, [Amim]Cl, [Epyr]BF4, [Bpyr]PF6, [Mpyr]Cl, [Empy]Tf2N, [PhPy]BF4 or [Et3NH]HSO4.

4. The preparation method according to claim 1, characterized in that The organic silicon source modifier described in step (2) is one or a combination of two or more of water glass, tetraethyl orthosilicate, methyl orthosilicate, methyl triethoxysilane, methyl trimethoxysilane, polyethoxy disiloxane, dimethyl dimethoxysilane, dodecyl trimethoxysilane or polydimethylsiloxane.

5. The preparation method according to claim 1, characterized in that The infrared shielding agent described in step (3) is a functional particle formed by inorganic nanoparticles with near-infrared shielding ability, which is LaB6, CuS, PbS, ZnS, Si3N4, TiO2, M x One or more combinations of WO3 (M = Na, Li, K, Rb, Cs), ITO, ATO or AZO.

6. The preparation method according to claim 1, characterized in that In step (3), the ultraviolet absorber is one or more combinations of UV-P, UV-O, UV-9, UV-326, UV-328, UV-531, UVP-327, RMB, AM-101 or GW-540.

7. The preparation method according to claim 1, characterized in that In step (4), the temperature of the vacuum drying oven is 50-85° C., the vacuum degree is 0.01-0.1 MPa, and the insulation time is 1-5 h. The molding process device in step (5) is: casting method, dipping-pulling method, spin coating method or spraying method.

8. The preparation method according to claim 7, characterized in that The process parameters of the casting method are: the casting rate is 1-300 ml / min, and the casting time is 1-5 min; the process parameters of the immersion-pulling method are: the pulling rate is 0.1-2 cm / s, and the pulling time is 1-3 min; the process parameters of the spin coating method are: the rotation rate is 300-2000 rpm, the spin coating acceleration is 50-500 rpm / sec, and the spin coating time is 0.5-3 min; the process parameters of the spray coating method are: the spray coating rate is 1-200 ml / min, and the spray coating time is 1-10 min.

9. The preparation method according to claim 1, characterized in that The aging liquid in step (7) is one of methanol, anhydrous ethanol, n-propanol, isopropanol, butanol, n-pentanol, hexanol, cyclohexanol or tert-butanol or a mixture thereof; the number of solvent replacements is 2 to 5 times, with an interval of 2 to 6 hours each time.

10. The preparation method according to claim 1, characterized in that The drying method in step (8) is atmospheric pressure drying, freeze drying, and carbon dioxide supercritical drying; the process parameters of the atmospheric pressure drying method are: temperature of 25 to 80° C., drying time of 12 to 48 hours, the process parameters of the freeze drying method are: freezing temperature of -80 to -20° C., baffle temperature of 15 to 30° C., drying time of 24 to 48 hours, and the process parameters of the carbon dioxide supercritical drying method are: temperature of 45 to 50° C., pressure in the autoclave of 9 to 12 MPa, degassing rate of 2 to 8 L / min, and drying time of 6 to 12 hours.